Fractal characteristics of shales from a shale gas reservoir in the Sichuan Basin, China - Yang, Feng; Ning, Zhengfu; Liu, Huiqing (Fuel (Guildford), 2014)
•Pore structure of shale was studied from fractal perspective.•Shales samples with higher TOC have greater fractal dimension.•Micropores have a greater impact on fractal dimension than mesopores and macropores.•Shale samples with a higher fractal dimension have greater adsorption capacity. Nanopore structure greatly affects gas adsorption and transport in shales. Such structures in shale samples from the Lower Cambrian strata of the Sichuan Basin of China have been investigated using X-ray diffraction, total organic carbon content (TOC) tests, porosity and permeability tests, nitrogen adsorption, and methane adsorption experiments. Fractal dimensions were obtained from the nitrogen adsorption data using the Frenkel–Halsey–Hill method. The relationships between TOC, clay minerals, pore structure parameters and fractal dimension have been investigated. Based on the physical description of the fractal surfaces, the impact of fractal dimension on adsorption capacity has also been discussed. The results showed that the shale samples had fractal geometries with fractal dimensions ranging from 2.68 to 2.83. The organic matter is a controlling factor on fractal dimension, shown by positive correlation between TOC and fractal dimension. Fractal dimension increases with increasing surface area and pore volume, and also increases with decreasing pore diameter because of the complicated pore structure. Micropores have a greater impact on fractal dimension than mesopores and macropores. A negative correlation between fractal dimension and permeability was observed, especially for shales with high TOC and micropores counts. The fractal dimension can be used to evaluate adsorption capacity. Shale samples with larger fractal dimensions have higher methane adsorption capacity. Fractal analysis leads to a better understanding of the pore structure and adsorption capacity of a shale gas reservoir.